A Comparative and Descriptive Study of Asthma in Chronic Rhinosinusitis with Nasal Polyps. Issue 5 (September 2014) - Håkansson, Kåre; Thomsen, Simon Francis; Konge, Lars; Mortensen, Jann; Backer, Vibeke; von Buchwald, Christian
Background: Chronic rhinosinusitis (CRS) is a common health problem that is subclassified as CRS with nasal polyps (CRSwNPs) or CRS without NPs (CRSsNP). In accordance with the united airways concept, CRSwNPs frequently coexists with asthma but to date, this association remains unexplained and its strength is uncertain. Here, we aimed to examine the association between CRSwNPs and asthma in collaboration between the neighboring specialities: otorhinolaryngology and respiratory medicine. Methods: A prospective clinical study was performed comprising 40 CRS patients scheduled for functional endoscopic sinus surgery and 21 control persons. We performed nasal endoscopy, peak expiratory flow, spirometry, and bronchodilation tests. In selected cases, additional pulmonary tests were performed. Atopy was assessed by skin-prick test or by measuring specific IgE in serum. Results: Asthma was diagnosed in 26 patients with CRSwNPs (65%; odds ratio = 5.9 [1.79, 19.65]; p = 0.003), and 5 control persons (24%). Twenty-five percent of the CRSwNP patients had undiagnosed asthma. Atopy was not significantly associated with CRSwNPs (p = 0.39) or with coexisting asthma within the CRSwNP group (p = 0.50). Conclusion: Compared with previous studies, we found a very high prevalence of asthma and, frequently, asthma was undiagnosed. Furthermore, CRSwNPs was associated with chronic bronchitis and, in those with asthma, lower airway obstruction. These results call for a closer collaboration between otorhinolaryngology and respiratory medicine in relation to patients with CRSwNPs, in research as well as in clinical practice.